Toward a decolonial pedagogy in Latin America: Convergences between popular education and participatory action research - João Colares da Mota Neto (Arizona State University, 2018)
The article analyzes possibilities of convergence between popular education and participatory action research, taking as a reference the thought of the Brazilian pedagogue Paulo Freire and the Colombian social scientist Orlando Fals Borda. In particular, it examines these convergences in order to identify elements for the constitution of a decolonial pedagogy in Latin America. It is a research inserted in the field of the comparative history of Latin American social thought, using as primary sources several works of Paulo Freire and Orlando Fals Borda. The article defends the argument that the convergence between popular education and participatory action research is one of the most fruitful, creative and instigating intellectual contributions ever produced in Latin America, capable of pointing to a decolonial pedagogy that confronts intellectual colonialism, Pedagogical traditionalism and the authoritarianism of modern-colonial science.